Risk Factors of Macrosomia in the Blang Bintang Community Health Center, Aceh Besar - Juliaastuti Juliaastuti; Cut Yuniwati (Health Notions, 2019)
Macrosomia is one of the important causes of fetal and maternal morbidity and mortality. Data from the Aceh Health Office in 2018 showed that the incidence of macrosomia was 7.7%. In Aceh Besar district the prevalence of obese children was 2.9%. The purpose of this study was to determine the risk factors of macrosomia birth in the work area of Blang Bintang Community Health Center, Aceh Besar in 2018. This study used a quantitative method with an analytical survey approach with a case-control design and was retrospective. Population in this study consisted of all infants who met the inclusion and exclusion criteria. A sample of 40 infants was selected by purposive sampling. The results showed that there was a risk of pregnant mothers who suffered diabetes mellitus and a history of previous macrosomia births with the incidence of macrosomia birth. While pregnant mothers who consume junk food and parity did not have the risk of macrosomia birth. Keywords: macrosomia; diabetes mellitus; junk food; parity; macrosomia history